KATA SERAPAN DARI BAHASA HAKKA DALAM LEKSIKON BAHASA INDONESIA - Manzhuur Daanisy Ahmad Thaahir Pontoh; Assa Rahmawati Kabul (SEMIOTIKA: Jurnal Ilmu Sastra dan Linguistik, 2023)
Indonesian language borrowed heavily from languages spoken inside Indonesian territory. The borrowing is caused by language contact between Malay (and now Indonesian) and other languages, including several Sinitic languages that have been spoken for centuries in Indonesia. Hakka Chinese is one of the largest Sinitic languages in Indonesia by the number of speakers, therefore borrowing from Hakka Chinese in Indonesian is bound to happen. The aim of this research is to find borrowings from Hakka Chinese in Indonesian lexicon, also to find semantic changes in those borrowings. Methods in finding the borrowings started from compiling all the possible Hakka loanwords from Hakka lexicons into a wordlist. The wordlist is verified by native Indonesian Hakka Chinese correspondent, and then compared to lemmas in the Kamus Besar Bahasa Indonesia (KBBI) to find any semantic changes. We found that there are 44 loanwords from Hakka Chinese in Indonesian, of which 15 words had semantic changes and 29 others have not any semantic changes.